Analisis Pengaruh Net Profit Margin (NPM) dan Total Assets Turnover (TATO) Terhadap Return on Assets (ROA) pada Perusahaan Industri Logam dan Mineral yang Terdaftar di BEI - Pina Aulia Maharani; Wahidah Nazmi Lailia; Mila Salbiyah; Alfiana Alfiana (Indonesia Economic Journal, 2026)
Financial performance reflects a company's ability to manage its resources efficiently. One commonly used measure of financial performance is Return on Assets (ROA), which indicates a company's ability to generate profits from its total assets. Fundamental factors that can affect ROA include Net Profit Margin (NPM), which reflects a company's ability to generate net profit from sales, and Total Asset Turnover (TATO), which indicates a company's effectiveness in utilizing assets to generate revenue. This study aims to analyze the effect of NPM and TATO on Return on Assets (ROA) as a proxy for financial performance in Industry Metals and Minerals companies listed on the Indonesia Stock Exchange. The benefits of this study are expected to provide input for company management as well as serving as a reference for investors before making investment decisions. The research method uses a quantitative approach with panel data regression analysis of the company's financial statements during the research period. The results of this study are expected to strengthen empirical evidence regarding the effect of NPM and TATO on ROA as indicators of company financial performance.